2018
DOI: 10.1111/liv.13715
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the radioactive copper incorporation test in the diagnosis of Wilson disease

Abstract: The radioactive copper test had excellent diagnostic accuracy and may be useful in the evaluation of new therapies aimed at restoring ATP7B function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…The use of radioactive Cu isotopes to assess copper metabolism in humans was introduced decades ago, and many studies on this topic have been published since then (Sternlieb and Scheinberg 1972;Gunther et al 1975;Harvey et al 2005;Czlonkowska et al 2018). Most recently, Czlonkowska et al showed that measurements of 64 Cu in blood and in urine following intravenous injection accurately distinguished between patients with Wilson's disease and heterozygote controls (Czlonkowska et al 2018). The obvious advantage of 64 Cu-copper PET/CT is however, the potential for assessing also the hepatic uptake, accumulation, and turnover; this includes oral administration where the biodistribution is dominated by first pass extraction by the liver, as demonstrated in the present study.…”
Section: Copper Metabolismmentioning
confidence: 99%
“…The use of radioactive Cu isotopes to assess copper metabolism in humans was introduced decades ago, and many studies on this topic have been published since then (Sternlieb and Scheinberg 1972;Gunther et al 1975;Harvey et al 2005;Czlonkowska et al 2018). Most recently, Czlonkowska et al showed that measurements of 64 Cu in blood and in urine following intravenous injection accurately distinguished between patients with Wilson's disease and heterozygote controls (Czlonkowska et al 2018). The obvious advantage of 64 Cu-copper PET/CT is however, the potential for assessing also the hepatic uptake, accumulation, and turnover; this includes oral administration where the biodistribution is dominated by first pass extraction by the liver, as demonstrated in the present study.…”
Section: Copper Metabolismmentioning
confidence: 99%
“…Ceruloplasmin (enzymatic) ferroxidase activity could aid in the direct quantification and speciation of copper in plasma, but it is not normally provided in clinical practice. Other parameters, including radioactive copper incorporation and exchangeable copper, appear promising and could potentially enable a better assessment of copper status, but remain unvalidated [32,33]. To study the effects of dietary components such as sugar consumption on transition metal levels and the resulting metabolic changes, improved clinical parameters for assessing these metal levels are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…DNA analyses with Sanger's sequencing method showed two variants classified as disease-causing variants in the Wilson Disease Mutation Database (http://www.wilsondisease.med. This test measures the incorporation of radioactive intravenous copper into ceruloplasmin and involves the assessment of blood radioactivity after 2 (the starting value), 24, and 48 hours [6]. In healthy people, radioactive copper accumulates in the liver after a few hours, forms ceruloplasmin and is released into the blood, with almost all radioactive copper found in the blood after 24-48 hours.…”
Section: To the Editorsmentioning
confidence: 99%
“…In WD patients, 24 hour/2 hour and 48 hour/2 hour 64 Cu ratios are generally ≤ 0.36 and ≤ 0.4, respectively [6]. This test reflects the functional activity of the copper transporter ATP7B and is characterised by very high sensitivity (48 hour/2hour 64 Cu ratio -98.6%) and specificity (48 hour/2hour 64 Cu ratio -100%).…”
Section: To the Editorsmentioning
confidence: 99%